Overview of the Standards and Objectives of Implementing the Dengue Hemorrhagic Fever (DHF) Control Policy through the One House One Mosquito Net Movement Program at the Rahandouna Village Health Center, Kendari City - Muhammad Arsyi, La Ode; Azizi Jayadipraja, Erwin; Abdurrahman, Syawal (Magister Kesehatan Universitas Mandala Waluya, 2025)
Introduction:Dengue fever remains a serious health problem in Indonesia, including in Kendari City, with cases occurring annually. In 2023, Kendari City successfully reduced dengue fever morbidity through the